Balancing Educational Practice with Psychological Theory: Lukinsky's Study of a Bold Camp Ramah Curriculum. Issue 2 (2nd April 2016) - Reimer, Joseph
Abstract: Missing from the growing literature on Jewish camps is Lukinsky's (1968) pioneering study of the curriculum to teach responsibility that he designed for the 1966 Ramah American Seminar. Reviewing this work I discovered that Lukinsky—under Schwab's (1971) influence—creates a rare balance between his own perspectives as an educational practitioner turned researcher with those of Erik Erikson, the famed developmental psychologist. I suggest that we read his work as an example to all who call upon theories of psychological development on how to use those theories to illuminate our thinking while not allowing them to dominate our educational discourse.